The Prediction of Lithium Battery Life in Cellular Telecommunication Stations - Panya Khemmook; Worapong Pairindra; Teeraphon Phophongviwat (2022 International Electrical Engineering Congress (iEECON), 2022)
This research paper introduces the remaining useful life prediction of lithium batteries operating at 48 V, 100 Ah on the cellular telecommunication substation with the load supply current conditions 1C rate at 100% DOD. According to the prediction technique, a 100-cycle of experimental results of actual discharge time are used to create the equation by using the curve fitting technique. Finally, the obtained results can estimate the battery lifetime and identify the time which will be able to supply the battery's load if the battery is operated under any conditions.
Keywords: Advanced Battery Technologies Research; Energy Harvesting in Wireless Networks; Electric Vehicles and Infrastructure